Mentoring Experiences and Latina/o University Student Persistence. (October 2014) - Salas, Richard; Aragon, Antonette; Alandejani, Jehan; Timpson, William M.
This study examined the experiences of 17 Latina/o students who participated in a university mentoring program that included academic and cultural resources, involvement, and leadership opportunities. The goal was to understand their lived experiences and their own perceptions of their academic success and persistence. An interpretive phenomenological analysis was used with one-on-one interviews, revealing the following emergent themes: (a) common experiences providing benefits of mentoring, (b) common challenges, and (c) lessons learned.